Modifications of cellulose-based biomaterials for biomedical applications - Fatema, Nour; Ceballos, Ruben Michael; Fan, Chenguang (Frontiers in Bioengineering and Biotechnology, 2022)
Cellulose is one of the most abundant organic compounds in nature and is available from diverse sources. Cellulose features tunable properties, making it a promising substrate for biomaterial development. In this review, we highlight advances in the physical processes and chemical modifications of cellulose that enhance its properties for use as a biomaterial. Three cellulosic products are discussed, including nanofibrillated, nanocrystalline, and bacterial cellulose, with a focus on how each may serve as a platform for the development of advanced cellulose-based biomaterials for Biomedical applications. In addition to associating mechanical and chemical properties of cellulosic materials to specific applications, a prospectus is offered for the future development of cellulose-based biomaterials for biomedicine.